WHAT A SHOCKING ISLAMIC EDUCATION (Between Reality and Expectations) (International Conference on Social and Islamic Studies, 2022)
This article talks about education now and the future, of course, cannot be separated from historical nostalgia about Islam and the peak of its civilization in the past. The method uses a library research and data from books, journals, and others. So, in this case before the power of science raised the spirits of Westerners (renaissance), al-Siba'i said that Islam had experienced its golden age, while Europe was confined by a dark. It reads a terrible condition, where Islam is busy with scientific studies so that it gives birth to a civilization that has a very high value, unlike the Western world which closes rationality and relies on mystical. If it can be said, Islam is currently still shackled or "hasn't moved on" to historical romanticism in the past, in the sense that it still uses "old clothes" because it has had a long history of questioning world civilization and influential scholars. Then forgetting today’s reality, Islam is powerless against the currents of modernism. Therefore, it is deemed necessary to photograph educational problems in terms of ontology, epistemology, and axiology aspects.